Nasafi's view of mystic's journey - Ehsan Reisi (ادبیات عرفانی, 2015)
The journey can be considered as the most important element of mysticism and its distinguishing factor against all other wisdom systems. Accordingly, this issue has always been at the focus of attention among mystic people, and therefore, a large part of mystical texts has been dedicated to explaining how the journey is. The existence of various plans for stages and habitations of the journey indicates the presence of traditions, schools, educational systems and various mystical experiences in Islamic mysticism. Thus, the analysis of the theoretical and intellectual foundations of the mystics on the perfection course plays a very important role in understanding these topics.Aziz ibn Muhammad Nasafi, as a creative and innovative mystic in theological, ontological and anthropological matters, has provided significant standpoints about the journey. In this article, we review and analyze the mentioned standpoints and clarify Nasafi's intellectual foundation on the journey of perfection.Although Nasafi has provided several plans for the journey, the foundation of all these plans is based on two pillars: 1. Attention to the seeker's inside; 2. Attention to the seeker's outside. In addition, "changing the potentials into actions" is of particular importance to achieve perfection in the plans he has presented.